Seasonal Diversity of Butterflies in the Fragmented Habitats of Waghai Botanical Garden of The Dangs - Gujarat - Gandhi, Suchi; Kumar, Dolly (International Journal of Biological Research, 2016)
Background: The world is currently undergoing a very rapid loss of butterfly biodiversity comparable with the great mass extinction events that have previously occurred only five or six times in the Earth’s history. This is an alarming call of these tiny scraps of biodiversity which now have scarce appearance surrounding the huge human kingdom.Objective: The richness of biodiversity depends on the climatic conditions and area of the region. The present research work focuses on studying butterflies diversity, their habitat preferences and seasonal distribution in structured plots of Waghai Botanical Garden.Method: For carrying out systematic study, Waghai Botanical Garden was fragmented into five sub habitats i.e. Dry & Moist Deciduous plot, Evergreen plot, Bamboo plot & Dang plot, Scrub Thorn Forest & Medicinal & Taxonomy plot. Intra-individual comparative abundance study for observed butterfly species within fragmented plots of Waghai botanical garden was carried out graphically to study the butterfly’s preference in the plots of botanical garden.Results: Out of 70 species, the maximum number of species i.e. 27 species were observed from family Nymphalidae, followed by 18 species from Lycaenidae, 15 species from Pieridae, Papilionidae with 7 species and 3 species from Hesperiidae.Conclusion: During post-monsoon season, highest total average rainfall of around 850 mm was observed in Waghai during monsoon, which provided excellent quality and quantity of larval food plants for the caterpillars and nectar rich flower source for adult butterflies in post-monsoon months. Thus maximum numbers of butterflies’ species were observed during the months of October & November.